Leg Muscle Training Increases Sickle Kick Speed in Pencak Silat Athletes: Latihan Otot Tungkai Meningkatkan Kecepatan Tendangan Sabit Atlet Pencak Silat - Nasyiri, M.Raihan; Saputra, Deka Ismi Mori; Pilitan, Raja Bani (Universitas Muhammadiyah Sidoarjo, 2026)
This study addresses performance development in pencak silat, emphasizing the role of physical conditioning in technical execution. General Background: Pencak silat performance relies on the integration of physical fitness and technical skills, particularly in executing effective kicking techniques. Specific Background: The sickle kick is a fundamental offensive technique requiring optimal leg swing, body stability, and hip rotation, yet athletes at Perguruan Margaluyu 151 demonstrate low kick speed due to insufficiently targeted leg muscle training. Knowledge Gap: Existing training programs emphasize technique without structured focus on leg muscle strengthening, limiting the transfer of physical capacity to kick performance. Aims: This study aims to analyze the effect of leg muscle training on improving sickle kick speed. Results: Using a quasi-experimental one-group pretest–posttest design with 30 male athletes, results show a mean score increase from 15.9 to 22.1, with a paired sample t-test value of -17.147 and significance of 0.000 (<0.05), indicating a significant improvement. Novelty: This study provides a specific analysis linking leg muscle training to sickle kick speed within a real training context at the perguruan level. Implications: The findings suggest that structured leg muscle training contributes to measurable improvements in kick speed and supports the development of targeted training programs aligned with athlete performance needs. HIGHLIGHTS • Leg-focused training produced measurable gains in kick execution speed• Athlete performance shifted from moderate to higher skill categories• Statistical testing confirmed significant pretest–posttest differences KEYWORDS Leg Muscle Training; Sickle Kick Speed; Pencak Silat; Quasi Experimental Design; Athletic Performance